2008
DOI: 10.1021/jf800849a
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Structural Characteristics of the Arabinogalactan−Protein (AGP) Fraction of Gum Arabic

Abstract: The structural characteristics of the gum exudate of Acacia senegal (gum arabic) have been investigated by monitoring the composition and physicochemical properties before and after treatment with proteolytic enzyme and various alkaline systems. Molecular mass ( M w) and radius of gyration ( R g) measurements were performed using gel permeation chromatography (GPC) coupled to refractive index, UV absorbance, and multiangle light scattering detectors and indicated that the macromolecules present have a compact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
123
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(132 citation statements)
references
References 37 publications
8
123
0
1
Order By: Relevance
“…Despite having different protein content, amino acid composition is similar in both gums. Recently, Mahendran et al, 2008, reported the GA amino acid composition in Acacia Senegal, being rich in hydroxyproline, serine, threonine, leucine, glycine, histidine, (Osman et al, 1993 andWilliams& Phillips, et al, 2000). Table 2.…”
Section: Chemical Composition and Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Despite having different protein content, amino acid composition is similar in both gums. Recently, Mahendran et al, 2008, reported the GA amino acid composition in Acacia Senegal, being rich in hydroxyproline, serine, threonine, leucine, glycine, histidine, (Osman et al, 1993 andWilliams& Phillips, et al, 2000). Table 2.…”
Section: Chemical Composition and Structurementioning
confidence: 99%
“…Table 2. Aminoacid content in Gum Arabic taken from Acacia senegal (Mahendran et al, 2008). Table 3 shows some physicochemical properties used as international GA quality parameters, for example: moisture, total ash content, volatile matter and internal energy, with reference to gums taken from Acacia senegal species in Sudan (FAO, 1990, Larson & Bromley, 1991.…”
Section: Chemical Composition and Structurementioning
confidence: 99%
“…It is suggested that the high-molecular-weight fraction of the gum consists of large carbohydrate blocks with a molecular mass of approximately 2.5 · 10 5 Da attached individually to a polypeptide chain. GA is obtained from the stems and branches of Acacia Senegal and Acacia seyal, and being a branched polysaccharide, it exhibits unique structural, physical and chemical properties [84][85][86][87]. Consequently, it is widely used in food and pharmaceutical applications [88][89][90].…”
Section: Tree Gums -An Overviewmentioning
confidence: 99%
“…The polysaccharide component represents approximately 95% of the macromolecule and consists of a very complex, heavily branched β(1 3)D-galactopyranose backbone with a high proportion of arabinofuranose and rhamnopyranose residues (5) and terminal glucuronic acids. The protein component consists of a 250 amino acid chain, with regions of polysaccharide covalently O-linked to hydroxyproline and serine residues (6). This is often referred to as the wattle blossom model (3).…”
Section: Introductionmentioning
confidence: 99%
“…The overall hydrodynamic structure has previously been studied principally using light scattering and chromatographic based methods (6). From these, the "wattle blossom" model appears to have become favoured, with the overall conformation of the molecule being close to spherical.…”
Section: Introductionmentioning
confidence: 99%